Alliances to transform: Young livestock producers and the impact of farmer training programs, the case of “Heirs of Tradition” - Triana Ángel, Natalia; Ariza-Aya, Mauricio; Arango, Jacobo; Burkart, Stefan (Bioversity International and the International Center for Tropical Agriculture, 2022)
Insufficient schooling rates among livestock producing families are pivotal in preventing an effective generational transfer and gender and social equality in Colombia’s rural settings. Concurrently, low literacy rates are now understood as a critical factor hindering the livestock sector’s productivity and sustainability. Even though several academic readings and approximations to Colombian rurality have stressed the importance of educational opportunities as mean to effectively integrate national peasantry and promote equality, coverage still falls short. In this study we address these subjects through the examination of the case study “Heirs of Tradition”, an initiative carried out by Alquería, a major Colombian dairy company. Our objectives are to assess the impact achieved in terms of generational transfer and gender equality in a modernizing dairy sector. We based our analysis on in-depth interviews and the review of primary sources from the company’s own archive and secondary, scientific and academic sources. Findings suggest that cooperation between actors is key to address generational transfer and that education and technical support can both reduce low schooling rates amongst rural livestock producers and contribute to closing the gender gap that persists in the sector. We also highlight the achievements and lessons learned, underscoring the issues that could be better addressed and overall emphasizing how the continuity of such programs favors knowledge transfer and empowers communities.